Tinjauan Yuridis Peyelenggaraan Pemerintahan Daerah Provinsi Yang Bersih Korupsi, Kolusi, dan Nepotisme Menuju Good Governance - Ama, Jefrianus Tamo; Kadir, Syukron Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The central government and provincial regional governments have close relations. There are at least four factors in the relationship between the Central Government and regional governments that determine the relationship between the Central Government and Regional Governments, including: Authority relationships, financial relationships, supervisory relationships, and relationships arising from the structure of regional government organizations. The position of the Regional People's Representative Council (DPRD) before the enactment of Law no. 32 of 2004 concerning Regional Government has differences. The position of the Regional People's Representative Council (DPRD) in Law no. 22 of 1999 concerning Regional Government, the difference is: In Law no. 32 of 2004, the position of the DPRD is as a Regional People's Representative Institution and has the role of organizing element of regional government (Article 40). Meanwhile, in Law no. 22 of 1999, the position of the Regional People's Representative Council is as a Regional Representative institution which is representative of democracy based on Pancasila and as a regional legislative body which has an equal position and is a partner of the Regional Government (article 16). Good governance is something that is very crucial for the government to pay attention to in carrying out and carrying out its role in accordance with its functions and duties so that it complies with legal provisions.